Correction: Effectiveness of Neurofeedback-Assisted and Conventional 6-Week Web-Based Mindfulness Interventions on Mental Health of Chinese Nursing Students: Randomized Controlled Trial - Shu Jing; Zhenwei Dai; Xiaoyang Liu; Xuelin Yang; Jinglei Cheng; Tianming Chen; Zihang Feng; Xin Liu; Fenghe Dong; You Xin; Zhuoyan Han; Haiyan Hu; et al. (Journal of Medical Internet Research)
In “Effectiveness of Neurofeedback-Assisted and Conventional 6-Week Web-Based Mindfulness Interventions on Mental Health of Chinese Nursing Students: Randomized Controlled Trial” (J Med Internet Res 2025;27: e71741.) the authors made fourteen clarifications.